Strategi Penguatan Legalitas Produk melalui Sertifikasi Halal pada UMKM Manisan Bligo - Aldillah, Rozak; Faisaldi, Rofik Hanif; Ainur, Shinta; Shofiyatul, Shofiyatul; Septian, Rizki (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The certification of halal products is essential for increasing consumer trust and market competitiveness, especially for small and medium-sized enterprises (SMEs). UMKM Manisan Bligo, a small business producing traditional candied winter melon, faces challenges in obtaining halal certification due to limited knowledge and resources. This community service program aimed to assist Manisan Bligo in the halal certification process through capacity building, document preparation, and procedural compliance. The implementation method using the Participatory Action Research (PAR) approach, involved training sessions, consultations, and direct assistance in fulfilling certification requirements. As a result, the business successfully completed the initial stages of certification and improved its understanding of halal production standards. This initiative not only enhances Manisan Bligo’s credibility but also serves as a model for other SMEs seeking halal certification. Strengthening business legality through halal certification is a strategic step to expand market access and support the sustainability of local SMEs.